Neural gliding versus tension in chronic discogenic sciatica - Omar Mohamed Albassiouny; Hala Rashad Ehabashy; Nawal Abdelraouf Aboushady; Wael Salah Shendy (Cairo : Omar Mohamed Albassiouny, 2017)
Background: Sciatica is a painful condition and can be a major cause of disability, work loss and presentation to health-care. Purpose: this study was to compare between the effect of gliding and tension techniques of neurodynamicmobilization tensionon pain intensity, latency and amplitude of H-reflex in patients with chronic discogenic sciatica. Subjects: Forty five male patients suffer from unilateral sciatica from disc lesion at L5-S1 for six months duration were selected from outpatient clinic of Kaser El Aini, Hospital and Faculty of Physical Therapy, Cairo University with age from40 to 55 years. They were divided into three equal groups; (A), (B) and (C). Procedure: Group A received selected physical therapy program (TENS and ultrasonic). Group B receivedselected Physical Therapy program, straight leg raising (SLR) and SLUMP neural glide exercises. Group C received selected Physical Therapy program and SLR and SLUMP neural tension exercises. For all groups treatment conducted for (4) weeks, (3) times per week, day after day, 45 min. per session. Measurement were taken before and after (4) weeks of the treatment. Measurement of pain carried out by Numeric Pain Rating Scale and assessment of the H-reflex amplitude and latency was done by Computerized Electromyography device. The results: Revealed that, there was a significant reduction of pain intensity in all groups (A, B and C) and significant reduction of H-reflex latency in both groups (B and C) (P<0.05). Comparison between post treatment values of pain,H-reflex amplitude and latency showed no significant difference between the three groups (p-value> 0.05). Conclusion: Both Neural gliding and Neural tension techniques of neurodynamic mobilization are effective in reducing pain intensity and H-reflex latency in patients with chronic discogenic sciatica
Thesis (M.Sc.) - Cairo University - Faculty of Physical Therapy - Department of Physical Therapy for Neuromuscular and NeuroSurgery
Issued also as CD
Keywords: Neural gliding; Strait leg raising; Tension